Comparing the bowel cleansing efficacy between sodium picosulfate vs. 2L polyethylene glycol electrolyte lavage solution for colonoscopy: a prospective observational study - Jing Shan; Yang Su; Dan Luo; Lin Jiang; Chen Zhang; Yifeng Liu; Xiaobin Sun (BMC Gastroenterology)
Abstract Background This study aimed to compare the bowel cleansing efficacy, adverse reactions, and patient compliance of two low-volume bowel preparation regimens, sodium picosulfate (PICO) and 2 L polyethylene glycol electrolyte lavage solution (2 L PEG-ELS). Methods This single-center, prospective observational trial was conducted at the Gastrointestinal Endoscopy Center of The Third People’s Hospital of Chengdu between May and October 2023. Patients undergoing colonoscopy were enrolled, with the primary outcome being the rate of adequate bowel cleansing, as assessed by the Boston Bowel Preparation Scale (BBPS) with three segments scoring ≥ 2. Secondary outcomes included polyp detection rate, adverse reactions, patient compliance, and the BBPS total and segment scores. Results A total of 5423 patients were included, divided into the PICO group (n = 739) and the 2 L PEG-ELS group (n = 4684) based on the bowel preparation regimen they chose. There were no statistically significant differences between the PICO and 2 L PEG-ELS groups in adequate bowel cleansing rate (92.2% vs. 91.3%, P = 0.437) and polyp detection rate (42.2% vs. 45.5%, P = 0.096). However, the PICO group achieved a better performance in the BBPS scores of the total [(6.90 ± 1.19) vs. (6.81 ± 1.14), P = 0.016] and the right colon [(2.15 ± 0.53) vs. (2.11 ± 0.51), P = 0.005] compared to the 2 L PEG-ELS group. In terms of adverse reactions, the 2 L PEG-ELS group reported more nausea (11.7% vs. 5.7%, P < 0.001) and the PICO group reported more sleep disturbances (24.5% vs. 14.6%, P < 0.001), but the willingness to repeat the procedure with the same regimen was similar high in the 2 L PEG-ELS and PICO groups (99% vs. 99.2%, P = 0.588). Conclusion In this prospective observational study, both PICO and 2 L PEG-ELS are safe and effective options for bowel cleansing in the Chinese population.